Downregulation of Microrna-126 in Scleroderma is Associated with Epigenetically Mediated Nitric Oxide Synthase Repression and Enhanced Platelet/Endothelial Interaction - Wang, Yongqing; Kahaleh, Bashar (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.